Endovascular management of pulmonary arteriovenous malformations presenting as multiple brain abscesses. Issue 11 (22nd November 2022) - Prasad, Surya Nandan; Sharma, Srishti; Singh, Vivek; Phadke, Rajendra Vishnu
Abstract : Pulmonary arteriovenous malformations (PAVMs) are rare vascular lesions characterised by abnormal connections between the pulmonary artery and vein bypassing the pulmonary capillary bed and causing right-to-left shunt. Paradoxical embolism is known to occur in these cases, leading to inoculation of septic focus in the systemic circulation. We report a case of multiple PAVMs who presented clinically with seizures and altered sensorium. On radiological work-up, multiple brain abscesses and large PAVMs were evident. The patient was successfully treated by endovascular embolisation of the PAVMs using a vascular plug and multiple coils. The patient showed complete clinical recovery and resolution of brain abscesses on follow-up.